Hubungan Implementasi Protokol Triase dan Response Time Terhadap Kepuasan Pasien Di IGD Rumah Sakit PMI Bogor - Gian Suherlan; Bambang Suryadi; Agus Purnama (Edukasi Elita : Jurnal Inovasi Pendidikan, 2024)
Introduction: Response time or speed in treating patients in emergency situations has a crucial role in saving lives. This includes the time required from when a patient experiences an emergency incident until the patient receives an appropriate medical response. In this context, it is important to understand that response times differ for different types of emergency cases. The aim of this research is to determine the relationship between the implementation of the Triage Protocol and Response Time and the Level of Patient Satisfaction in the Emergency Room at PMI Bogor Hospital.This research was quantitative using a correlation method involving 57 patients in the emergency room at PMI Bogor Hospital. To collect data, this study used prepared observation sheets, and statistical analysis was carried out using the Chi Square test. Patient Satisfaction Level effectively. With this approach, it is hoped that this research will provide valid and useful findings in supporting efforts to improve the quality of services at the Emergency Room at PMI Bogor Hospital.The results of chi-square statistical analysis showed that there was no significant relationship between the implementation of the triage protocol and patient satisfaction (p-value = 0.003 < 0.05). On the other hand, there is a significant relationship between the implementation of response time and patient satisfaction (p-value = 0.002 < 0.05). The faster the response time, the higher the level of patient satisfaction, in accordance with previous research findings